Developing advanced techniques to reclaim existing end of service life (EoSL) bricks – An assessment of reuse technical viability. (May 2020) - Zhou, Kan; Chen, Han-Mei; Wang, Yong; Lam, Dennis; Ajayebi, Atta; Hopkinson, Peter
Abstract: Structural bricks are highly durable building products. However, brickwork is mostly demolished long before the end of its technical service life; the majority are crushed to form aggregate or else landfilled. Urban mining and circular economy are stimulating interest in the potential to recover structural products from end-of-service-life buildings for direct reuse. For brickwork, separating bricks from cement-based mortar, as opposed to lime-based mortar, without damage to bricks is a major barrier. This paper presents two advanced techniques based on saw-cutting and punching, to demonstrate the technical feasibility of brick reclamation. Compared to new bricks, reclaimed bricks have similar visual appearance and their compressive strength differs by −4.8% to +40%. Design formula for compressive strength of masonry in current codes can be applied to reclaimed bricks. The reclamation process achieves reclaim rate of over 95% and has significantly lower energy consumption, and carbon requirements (<1%) relative to new bricks. Highlights: Bricks bonded by cement-based mortar can be reclaimed by saw cutting and punching. Reclaimed bricks have similar visual and aesthetic appearance as new bricks. Design formula for masonry compressive strength applies to reclaimed bricks. Brick reclamation processes require very low energy and low carbon. Advanced reclaiming techniques have a high potential to promote brick reuse.